The Use of Pirated Software During the Covid-19 Pandemic from Maqashid Shari’ah Perspective - Wahyu Sanjaya Putra; Nurhayati Nurhayati; Ramadhan Syahmedi Siregar (Jurnal Mahkamah : Kajian Ilmu Hukum Dan Hukum Islam, 2021)
The current Covid-19 pandemic has resulted in economic problems, but on the other hand, learning must still be carried out using computer or laptop technology that has software in it. The problem discussed in this article was how the law used pirated software during the Covid-19 pandemic. This research used a qualitative approach by interviewing students at the State Islamic University of North Sumatra. According to the results of the author’s research, it showed that this pandemic condition has changed the learning system from offline to online which had a huge impact on all levels of society. Copyright regulation and software requirements were needs that have reached the dharuri level and were included in the maqashid Sharia which aimed to maintain reason and protect human property so that they were not trapped and were not left in ignorance. Therefore, the result of this research was that the use of pirated software during the COVID-19 pandemic was permissible due to the pandemic period that has greatly changed the economic system of human beings, and will return to the original law, which was haram (forbidden) when this pandemic period ended, and the economy was back on its feet.